Women in the COVID-19 Pandemic: Analysis of Economic Resilience of MSME’s Actor's Family in West Denpasar District. - Prahastiwi, Anak Agung Rika; Saskara, Ida Ayu Nyoman (Jurnal Ekonomi Kuantitatif Terapan; 2023: Vol. 16, No. 1, Februari 2023 (pp.1-186)DO - 10.24843/JEKT.2023.v16.i01.p07, 2023)
MSMEs are assets that are owned to strengthen the foundation of the regional economy. United Nation Report (2020) states that MSMEs in the trade sector provide benefits for women in the post-COVID-19 recovery period. Not for women M SME in Bali. Supported by the characteristics of hardworking Balinese women, with a high work ethic, being in a cultu ral dress if work is a yadnya. The recommendation of this study is : reviewing how the economics resilience of M SME actors in facing the COVID-19 pandemic in West Denpasar District. The population is all MSME in Denpasar City with a non-proportional simple random sampling technique. Data analysis techniques used include descriptive analysis and binary logistic analysis. The results showed that the women MSME actors have stronger economic resilience than m en MSME actors . In addition to the high work ethic, also because women tend to be more creatively innovative in overcoming economic conditions. The implications of the results of the study should be policies related to MSMEs more gender responsive.